THE ADVANTAGES OF USING ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH - Qosimova Nodiraxon Sherali qizi; Yaqubjonova Roʻzixon Mirkomil qizi (TADQIQOTLAR, 2025)
Annotation: This thesis explores the integration of artificial intelligence (AI) into English language teaching, emphasizing the pedagogical benefits. The study also addresses how AI can assist teachers by automating administrative tasks and assessing student performance more efficiently. The research contributes to the growing field of educational technology by highlighting AI’s transformative role in language acquisition.